Singing voice range profile: New objective evaluation methods for voice change after thyroidectomy. (8th December 2020) - Seok, Jungirl; Ryu, Youn Mi; Jo, Seong Ae; Lee, Chang Yoon; Jung, Yuh‐Seog; Ryu, Junsun; Ryu, Chang Hwan
Abstract: Background: After surgery in the thyroid region, patients may present with phonation or singing difficulty, even within their vocal range. We designed a novel voice evaluation method that reflects subjective and objective voice complications of the surgery. Methods: This tool recorded patients' voice ranges while singing, which was named the singing voice range profile (singing VRP). Patients were asked to sing "Happy Birthday, " which has a one‐octave scale, at a comfortable tone and intensity. The singing VRP, standard VRP and voice handicap index‐10 (VHI‐10) results were recorded before thyroidectomy and 1 and 3 months after thyroidectomy for 128 patients. For subgroup analysis, a group where the maximum F0 of standard VRP in 1 month postoperatively was lower than the highest singing F0 of the preoperative singing VRP was defined as "Collapsed group" and the other group was "Preserved group." Results: The changes in the highest, lowest and range of singing fundamental frequency (F0 ) had decreased at 1 month postoperatively. Subsequently, they had improved significantly at 3 months postoperatively but were lower than those preoperatively (all P < .05, except for the change in the lowest singing F0 between 1 and 3 months postoperatively, P = .274). In the subgroup analysis, the singing range of the collapsed group (n = 65) showed significantly lower VHI‐10 scores, range of vocal F0 and singing F0 than those of the preserved group (n = 63) at 1 and 3 months postoperatively (all P < .001). At 3 months postoperatively, the singing F0 range in the preserved group had recovered to the range before surgery (13.0 ± 1.3 vs. 13.1 ± 1.4, P = .746 for the preserved group, and 13.0 ± 1.3 vs 11.5 ± 2.4, P < .001 for the collapsed group). Conclusions: Parameters measured by singing VRP showed a trend similar to the change in VHI‐10 and the maximum F0 of standard VRP. In addition, singing VRP allowed a qualitative classification of the postoperative voice function when combined with standard VRP. Therefore, it can be used as a supplementary voice evaluation tool to reflect the physiologic and functional aspects of voice.